LEARNING APPROACH BASED ON LOCAL WISDOM IN INDRAMAYU: A THEORETICAL REVIEW - Mardani, Dadan; Susiawati, Iis; Humaeroh, Iis; Utami, Dewi (ATTA`DIB, 2025)
Abstract This research aims to evaluate the effectiveness of local wisdom-based learning strategies in Indramayu, focusing on their impact on student engagement, understanding, academic achievement, and cultural appreciation. Utilizing a literature review method, this study examines existing research and documentation on the integration of local wisdom into educational practices. The findings indicate that such integration significantly enhances student involvement in the learning process, provides deeper comprehension of subjects, boosts academic performance, and fosters a greater appreciation for cultural heritage. The positive outcomes suggest that local wisdom-based learning strategies not only enrich the educational experience but also contribute to the preservation and appreciation of local.